A compelling case of postpartum symmetrical peripheral gangrene - Kizilay, Mehmet (The European Research Journal, 2020)
Symmetrical peripheral gangrene is one of the very rare problems that is usually secondary to intense inotropic therapy in critically ill patients, but also due to use of ergot alkaloids or sepsis in the postpartum period. We present a case of symmetrical peripheral gangrene developed in lower extremities of a woman in postpartum period ten days after discharge from hospital to which she was admitted and transfused 2 units of erythrocyte suspension due to significant bleeding following delivery conducted at home by an unskilled midwife in Mogadishu, Somalia. After pregnancy, whatever the cause, if developing symmetrical peripheral gangrene is not diagnosed in time and not treated as early as possible can cause limb loss and disability. Detection and investigation of this condition will also be enlightening for the mechanisms for ischemia and subsequent recuperation of circulation.